Fluorescent Detection of the Ubiquitous Bacterial Messenger 3′,5′ Cyclic Diguanylic Acid by Using a Small Aromatic Molecule - Xuan, Teng-Fei; Liu, Jun; Wang, Zi-Qiang; Chen, Wei-Min; Lin, Jing (Frontiers in Microbiology, 2020)
3′,5′ Cyclic diguanylic acid (c-di-GMP) has been shown to play a central role in the regulation of bacterial physiological processes such as biofilm formation and virulence production, and is regarded as a potential target for the development of anti-infective drugs. A method for the facile detection of the bacterial level of cellular c-di-GMP is required to explore the details of c-di-GMP signaling and design drugs on the basis of this pathway. Current methods of c-di-GMP detection have limited sensitivity or difficultly in probe preparation. Herein a new fluorescent probe is reported for the detection of c-di-GMP at concentrations as low as 500 nM. The probe was developed on the basis of the G-quadruplex formation of c-di-GMP induced by aromatic molecules. When used on crude bacterial cell lysates, it can effectively distinguish between the low c-di-GMP levels of bacteria in plankton and the high c-di-GMP levels in biofilm. The method described here is simple, inexpensive, sensitive, and suitable for practical applications involving the rapid detection of cellular c-di-GMP levels in vitro after simple bacterial lysis and filtration.